Belgacom Young Art : Année académique : 1997-1998. - van der Stighelen, Katlijne (Brussel : Belgacom, 1999)
Bil, Frederik ; Van Cauwenberghe, François ; Cheng, Pei-Lin ; Coolen, Caroline ; Cuvelier, Domitienne ; van Dijck, Bart ; Dupuy, Marie-France ; Fleury, Frédéric ; Goris, Ilse ; Govaert, Marilyne ; Lucet, Florent ; Plateus, Benoit ; Renneboog, Lucie ; Sotiere, Steve ; Sterckx, Klaar ; Stievenard, Dominique ; Tasiaux, Philippe
geboorteplaats en -datum
Frans & Nederlands
boek